Potensi Alellopati Ekstrak Gulma Alang Alang Sebagai Bioherbisida: Allelopathic Potential of Reeds Weed Extract as a Bioherbicide - Indarwati, Indarwati; Jili, Arsy Qova Andi; Susilo, Achmadi; Suryaningsih, Dwi Retna (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2023)
The aim of this study was to determine the Alellopathy Potential contained in Imperata cylindrica extract as a Bio-herbicide. The research was conducted at the Experimental Garden of the Faculty of Agriculture; Wijaya Kusuma Surabaya University. This research method used completely randomized design (CRD); with 4 treatments and 6 replications. The treatments are (A0): Control; A1 : extract concentration ( 250 g/L) ; A2 : 500g/L ; (A3); 750 g / L. Observational data were analyzed using Analysis of Variant (ANOVA), then tested with 5% BNT. The results showed allelopathy contained in the extract of Imperata cylindrica L. can suppress weed seed germination up to 94.67 %; and has a negative effect on the initial growth of spiny spinach (Amaranthus spinosus L) seedling sprouts. With treatment A2 and A3 ; All weed seeds that were able to germinate grew abnormally (100%). Imperata cylindica extract has the potential to be used as a bio-herbicide (natural herbicide) to suppress the early growth of weed seeds on spinach spines.